The compentences of the pedagogues in the context of a "learning society" - Slijepčević, Senka; Zuković, Slađana N (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper startsfrom the analysis of the connection between the development of post informatics society with modern pedagogical theory and practice.On the one hand, modern man is faced with great challenges and problems of today’s post informatics society. On the other hand, opportunities and different perspectives that individuals have in creating their own life path are extremely versatile. There are many trends of today’s world that influence daily life of every individual and some of those are: the age of instant communication, on-line learning, “age of leisure”, changes in business domain, “the triumph of individual”, etc. All of these trends, and many others, indicate the necessity of providing holistic and systematic support to upcoming generations. Educational institutions, which are the most organized forms of pedagogical work and influence, have to be the base for providing that support. Pedagogue plays crucial role in integrating the work of his educational institution with trends of our modern society. Therefore, emphasis of this paper is put on overview of key competences which pedagogues have to nourish and develop in changing conditions of modern world. In that regard, aim of this paper is directed towards analysis of the key competences important for the profession of pedagogue, which are based on the framework for 21st century teaching and learning (Partnership for 21st Century Skills). Those key competences are: learning and innovation skills, Information, media and technology skills and life and career skills. Learning and innovation skills are the first group of competences that are also referred as 4C since they include: Creativity and innovation, Critical thinking and problem solving, Communication and Collaboration. Second group of competences are centered around new digital media and technology, including practical skills of technology use, as well as ability to critically assess media content. Third group of 21st century key competencies are life and career skills which are emphasizing the importance of being adaptable, driven, reflective and prepared for a lifetime of learning and improvement. It can be concluded that key competence development among pedagogues, and among other educational staff, should ensure successful overcoming of current, and future, educational issues, as well as the quality and sustainability of education.